INFRASTRUCTURE FINANCING MODEL IN PUBLIC PRIVATE PARTNERSHIP - Dhifan Fadhilah Rizky Nurhadi; Muhamad Rizal; Anang Muftiadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Research aims: This study conducts a systematic literature review to explore the evolving landscape of sustainable infrastructure investment and financing by applying the PRISMA method and bibliometric analysis to 4,308 publications from 2009 to 2023. From this corpus, 74 peer-reviewed journal articles were selected for in-depth analysis based on their relevance and methodological rigor. Design/Methodology/Approach: This systematic literature review employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology to examine the financing and investment dimensions of sustainable infrastructure Research findings: The findings reveal that sectors such as renewable energy, green transportation, water and sanitation, healthcare, and digital infrastructure dominate discussions of sustainability due to their significant environmental and social impact. In terms of financing, traditional sources such as government budgets are being complemented by innovative mechanisms, including Public-Private Partnerships (PPPs), green bonds, ESG-linked financing, and blockchain-based tokenization. Furthermore, the study identifies a research trend toward the integration of Environmental, Social, and Governance (ESG) criteria, digital innovation, and collaborative governance as foundational elements of sustainable infrastructure development. This research contributes a conceptual framework for integrating green finance in sustainable infrastructure and highlights the interdisciplinary, technology-driven, and policy-relevant nature of this emerging domain.